2009
DOI: 10.1159/000219938
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of <i>I</i><sub>f</sub> Inhibition with Ivabradine in Different Subpopulations with Stable Angina Pectoris

Abstract: Objectives: The antianginal and anti-ischemic efficacy of ivabradine has been demonstrated in large-scale trials. Pooling trial data allowed for subpopulation analyses of ivabradine’s antianginal efficacy. Methods: Data on the frequency of angina attacks, short-acting nitrate consumption, and heart rate were pooled from 5 randomized trials in patients with stable angina pectoris receiving 5, 7.5, or 10 mg of ivabradine b.i.d. for 3 or 4 months. The subpopulations were defined according to age, sex, disease cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 62 publications
5
20
0
Order By: Relevance
“…Aged patients remain challenging to treat because of a higher prevalence of comorbidities and more frequent side effects or intolerance to drugs [24]. Reduction in angina attacks and consumption of short-acting nitrates has been previously shown in a subgroup of 91 elderly patients with stable angina in a pooled analysis of RCTs [16]. Here, we demonstrated the antianginal effectiveness of ivabradine in a sizeable population of more than 1,600 patients ≥75 years seen in real clinical practice.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Aged patients remain challenging to treat because of a higher prevalence of comorbidities and more frequent side effects or intolerance to drugs [24]. Reduction in angina attacks and consumption of short-acting nitrates has been previously shown in a subgroup of 91 elderly patients with stable angina in a pooled analysis of RCTs [16]. Here, we demonstrated the antianginal effectiveness of ivabradine in a sizeable population of more than 1,600 patients ≥75 years seen in real clinical practice.…”
Section: Discussionmentioning
confidence: 52%
“…Compared with pooled randomized trials with ivabradine [16], the patients in our study were older (≥75 years: 19 vs. 4%) and more often women (41 vs. 18%). They also presented with a higher heart rate at baseline (83.3 vs. 73.0 bpm) and more hypertension (91 vs. 59%), dyslipidemia (80 vs. 53%), diabetes (46 vs. 19%), and asthma/COPD (35 vs. 6%).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…16,17 The analysis of pooled data from ivabradine angina development programme assessing the antianginal efficacy of ivabradine is similar across several different subgroups of patients with stable angina selected on the basis of pretherapy characteristics or co-morbidities. 18 These results provide clinical evidence that ivabradine diminishes or prevents angina in all types of patients, independent of their baseline characteristics including age, sex, severity of angina, and revascularization status, as well as other features such as previous myocardial infarction, peripheral vascular disease, or diabetes. A reduction in HR of 11 b.p.m.…”
mentioning
confidence: 61%
“…9 Several studies have shown ivabradine to be noninferior to first-line antianginal agents, such as beta-blockers and calcium channel blockers, and superior to placebo. [10][11][12][13] Ivabradine has a class IIa (level of evidence B) indication for the symptomatic treatment of chronic stable angina in patients intolerant to or inadequately controlled by beta-blockers. 2 In this issue of Angiology, Zarifis et al 14 evaluated the potential antianginal effect of ivabradine when coadministered with beta-blockers in 926 patients with chronic stable angina and history of coronary revascularization (coronary artery bypass graft or percutaneous coronary intervention) in a time period of 4 months.…”
mentioning
confidence: 99%